THE PRINCIPLE OF ENSURING THE SUSPECT, THE ACCUSED THE RIGHT TO DEFENSE AND ITS RELATION TO OTHER PRINCIPLES OF THE CRIMINAL PROCESS (Journal of actual problems of jurisprudence, 2019)
The article discusses the principle of ensuring the suspect, accused the right to defense and its relation to other principles of the criminal process. Providing the defendant and the suspect the right to defense as a principle of justice and criminal procedure relies on constitutional and criminal justice rules.To date, the possibility of the participation of a lawyer in criminal proceedings has been markedly expanded. The purpose of this article is to consider the principle of ensuring that the suspect, accused person has the right to defense with other principles in the criminal process. The ability to determine whether the lawyer has sufficient funds for the successful implementation of the defense function. Ensuring that the suspect and the accused have the right to defense is organically derived from the presumption of innocence of the accused: the right to defense is required only for those who have not yet been convicted and only suspected and accused of committing a crime. The obligation to ensure the realization of the right of the suspect and the accused to defense is assigned to the state authorities conducting criminal proceedings and responsible for its successful completion. However, the principle of competition, which is fundamental and dominant in the current Criminal Procedure Code of the Republic of Kazakhstan, degrades, in our opinion, its own importance and interconnection between the principles of the presumption of innocence and ensuring the right to defense to the suspect and the accused. With the adoption of the new Criminal Procedure Code of the Republic of Kazakhstan, the extreme support of the adversarial process in the criminal process, characterized by a refusal to establish the truth, a fairly passive role of the court in proving, actually placing the responsibility of proving on the parties”, which could not but affect the very principle of ensuring the suspect and the accused protection. This principle is depleted, as it is carried out, in essence, only at the formal-legal level of competition and therefore is narrowly pragmatic in nature, which inevitably affects the very quality of such protection. The pre-trial investigation authorities are obliged to unswervingly comply with all the norms relating to ensuring the rights of the accused. Each of the violations of these norms ultimately leads to a violation of the principle of ensuring the defendant’s right to a defense and interferes with the establishment of the truth in the case. Key words: suspect, accused, defense, pretrial investigation, presumption of innocence, adversary.